The Big G and the Never-Ending Story of Knowledge Monopolies - Miconi, Andrea (Mediascapes journal, 2013)
In the critical trend in new media theory, which has taken place in recent years, the latest emerging question to be answered is: in which way software applications and search engines are shaping the architecture of the web, and affecting users’ behavior? Needless to say, Google has played a hugely influential role in the process by which the Internet has gone from an experimental and relatively free phase to becoming a contemporary mass medium, affected by centralization and ruled by what Jaron Lanier first defined as a “lock-in” effect...